(untitled) (Bangladesh Pharmaceutical Journal, 2024)
Catharanthus roseus, or ’Nayantara’ in Bengali, is a perennial flowering herb. This study aimed to evaluate the pharmacological effectiveness of the plant, focusing on its anti-diabetic, peripheral and central analgesic, and antidiarrheal effects. Methanol soluble partition 200 (MSP-200) and 400 (MSP-400) mg/kg body weight were administered for glucose tolerance test (GTT), heat and chemical-induced response tests, sodium thiosulphate induced test, and castor oil induced test, evaluating anti-diabetic, peripheral and central analgesic, and antidiarrheal effects via in-vivo assay in Swiss-Albino mice model. Methanol soluble partition (MSP) at 200 and 400 mg/kg doses significantly reduced the blood glucose levels of mice by 31.00% and 32.97%, respectively (standard 46.24%). In peripheral analgesic activity, MSP-400 (62.82 ± 4.62%) outperformed MSP-200 (50 ± 3.62%) and MSP-200 (p = 0.0001) exhibited statistically significant central analgesic activity. MSP-400 demonstrated potent anti-diarrheal activity (p = 0.0002). The outcomes from this study put forward a cogent argument that C. roseus plant is capable of producing numerous bioactive compounds such as flavonoids, alkaloids, terpenoids, tannins, etc. which requires systematic phytochemical and pharmacological investigations. Bangladesh Pharmaceutical Journal 27(2): 215-222, 2024 (July)